Towards a Discourse Move Analysis of Research Article Abstracts in Nepali Journals: A Cross-Disciplinary Study - Paudel, Pitambar (Prithvi Academic Journal, 2024)
An abstract is an important component of a research article to attract the readers’ attention and provide a concise, informative, and accurate summary of the paper. Many academic manuscripts are usually rejected due to ineffective abstracts. This study aims to investigate and analyse the discourse moves in research article abstracts in the journals published in Nepal. To achieve this objective, 120 article abstracts from journals of eight different domains were selected, and the contents were analysed using Bitchener’s (2018) framework. The results showed that all the abstracts followed the broad categories of introduction, purpose, methods, products, and conclusion, but there were differences in frequency of occurrence using the parameters specified under each category. The findings of the study showed that discourse moves were frequently used by the majority of journals for writing the context and background, authors' motivations for the research, research gaps, goals of the research, research approach and design, data sources and analysis processes, findings, and contributions of the findings to related fields. Finally, the study concluded that the findings of the study can be significant for designing field-specific academic writing courses that lead the authors to standardize their writing and prevent the article from being rejected.